Analisis Perilaku Harian Bangau Tongtong (Leptoptilos javanicus) di Taman Margasatwa Ragunan - Cantika Choirunisa; Dini Safitri; Refirman Djamahar (Universitas Nusantara PGRI Kediri, 2024)
Lesser Adjutant are included in the 2016 IUCN red list vulnerable status,because the number of Lesser Adjutant populations continues to decreasedue to disturbances to the Lesser Adjutant population. Conservation efforts areneeded to save the Lesser Adjutant (Leptoptilos javanicus). Conservation canbe done both outside its place of origin (ex-situ) and in its natural habitat(in-situ). One place that acts as a shelter and conservation site for LesserAdjutant, located in DKI Jakarta, is Ragunan Zoo. Ragunan Wildlife Parkserves as an area to protect and care for Indonesian animals, including LesserAdjutant. This study aims to observe the daily behaviour of Lesser Adjutant(Leptoptilos javanicus) in Ragunan Zoo. The research method used wasdescriptive qualitative method by observing daily behaviour in captivity. Dataanalysis techniques were carried out descriptively qualitative with observationtechniques accompanied by supporting photos. The results showed the dailybehaviour of Lesser Adjutant in captivity, namely eating, grooming, resistance,watching, and flying.